2009
DOI: 10.1021/ja807297g
|View full text |Cite
|
Sign up to set email alerts
|

LiCB11(CH3)12-Catalyzed Radical Polymerization of Isobutylene: Highly Branched Polyisobutylene and an Isobutylene−Ethyl Acrylate Copolymer

Abstract: In the presence of LiCB(11)Me(12) catalyst and a nonoxidizing radical initiator, isobutylene undergoes radical chain polymerization in an inert solvent at ambient temperature and pressure to give a new highly branched form of polyisobutylene. Copolymerization with ethyl acrylate is also possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 12 publications
4
58
0
Order By: Relevance
“…Lithium salts are also used in conjunction with aprotic dipolar solvents for cellulose dissolution and as reaction media [6][7][8][9][10]. Further examples of condensed-phase applications can be found in the domain of catalysis by weakly coordinated lithium cation [11][12][13][14][15] and hydrogen storage [16][17][18][19][20]. Analytical mass spectrometry makes use of the formation of gas-phase adducts with metal cations (a process often called cationization), and Li + has been extensively examined in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium salts are also used in conjunction with aprotic dipolar solvents for cellulose dissolution and as reaction media [6][7][8][9][10]. Further examples of condensed-phase applications can be found in the domain of catalysis by weakly coordinated lithium cation [11][12][13][14][15] and hydrogen storage [16][17][18][19][20]. Analytical mass spectrometry makes use of the formation of gas-phase adducts with metal cations (a process often called cationization), and Li + has been extensively examined in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Presently we examine the use of the LiCB 11 (CH 3 ) 12 catalyst with azo-tertbutane (ATB) radical initiator for the copolymerization of IB with ethyl acrylate (EA), as previously briefly mentioned in a short communication. 2 We find that it leads to an unusual somewhat branched nonalternating high molecular weight copolymer with up to ∼56 mol % of IB.…”
mentioning
confidence: 71%
“…Presently we examine the use of the LiCB 11 (CH 3 ) 12 catalyst with azo-tertbutane (ATB) radical initiator for the copolymerization of IB with ethyl acrylate (EA), as previously briefly mentioned in a short communication. 2 We find that it leads to an unusual somewhat branched nonalternating high molecular weight copolymer with up to ∼56 mol % of IB.EA and IB can be copolymerized, but it is difficult due to different reactivity. 4 IB is normally polymerized cationically to a linear polymer with AlCl 3 in halogenated hydrocarbons in the presence of traces of water.…”
mentioning
confidence: 79%
“…11 A practically important application of LiCB 11 Me 12 is catalysis of the radical polymerization of alkenes also reported by Michl. 12 In previous work 13 we demonstrated that chiral anionic complexes of potassium and silver K-or D-bis[N-salicylidene-(S)-aminoacidato]cobaltates 14 can be used as Lewis acid catalysts in asymmetric trimethylsilylcyanation of aldehydes and Mukayama aldol reaction. It was deemed interesting to extend this approach to examine C-C bond-forming reactions catalyzed by lithium Kor D-bis[N-salicylidene-(S)-aminoacidato]cobaltates.…”
Section: Introductionmentioning
confidence: 99%